The Effect of Group Guidance on Self-Management Techniques to Increase Students' Awareness of Time Management - Aisy, Alya Rihhadatul; Dalimunthe, Raudah Zaimah; Handoyo, Alfiandy Warih (Konseling Edukasi : Journal of Guidance and Counseling, 2023)
The Effect of Group Guidance on Self-Management Techniques to Increase Students' Awareness of Time Management. This research aims to determine the effect of group guidance using self-management techniques to increase awareness of time management among class VIII students at SMP Negeri 2 Menes for the 2023–2024 academic year. The population in this study was 90 students in class VIII at SMP Negeri 2 Menes. This research uses a pre-experimental method with a one-group pre-test and post-test design. Through a non-probability sampling method, the purposive sampling technique. The pre-test results showed that out of a total of 90 students, 3 were in the very low category, 39 were in the low category, 37 were in the high category, and 4 were in the very high category. Treatment was given to 8 students during 8 meetings. The research hypothesis test was carried out using the Wilcoxon test. There is a difference between time management abilities before and after treatment is carried out through group guidance with self-management techniques. With N = 8, the Z value is -2.524b, and the result is an Asymptotic Sig. (2-tailed) of 0.012. This value is smaller than 0.05, which means the hypothesis is accepted (Ha). From the results of these calculations, it can be concluded that group guidance using self-management techniques can increase awareness of time management among class VIII students at SMPN 2 Menes for the 2023–2024 academic year.Keywords: Group Guidance, Self Management Techniques, Student Awareness, Time Management